#TITLE_ALTERNATIVE# - HAMZAH NIM: 20214040, HARDI
Self-potential is a passive measurement method because the potential which generated by a number of natural resources of the earth without any injection into the subsurface utilizing the electric field arising from the natural current in the ground. Potential is measured on the surface less thanmil livolts up to one volt, as well as negative or positive signs of potential that obtained as an important factor for the interpretation of self-potential anomalies. Analysis of the causes in self-potential anomalies which is measured in the field can be done by using forward modeling and inversion of the finite element method using global optimization Very Fast Simulated Annealing (VFSA). Forward modeling with finite element method in the study is involved discretization domain, completion of the order differential equation in Poisson's equation with the approach Galerkin residual weighted and applying Green's theorem, selection of the right interpolation function, decreased matrix elements and vector elements, applied two boundary condition types Diriclet and Neumann, and the last is solution which obtained from the global matrix system formed. Field data is processed by inversion with global optimization VFSA to determine the physical structure below the surface.